2017
DOI: 10.1016/j.contraception.2016.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Does body mass index or weight perception affect contraceptive use?

Abstract: Overweight and obese women may be reluctant to use contraceptive methods they believe are associated with weight gain (i.e., pills, shot), but how that affects contraceptive use is unclear. Compared with normal-weight women, overweight and obese women in this study were more likely to use LARCs than non-LARC prescription methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 17 publications
0
15
0
1
Order By: Relevance
“…Contraceptive pills have not been associated with weight gain and mood changes. It is recommended to take single-phase pills in teenagers for their menstrual bleeding disorders [51][52][53][54][55].…”
Section: Contraceptive Pillsmentioning
confidence: 99%
“…Contraceptive pills have not been associated with weight gain and mood changes. It is recommended to take single-phase pills in teenagers for their menstrual bleeding disorders [51][52][53][54][55].…”
Section: Contraceptive Pillsmentioning
confidence: 99%
“…Fewer than half of the reviewed articles provided insight on women’s knowledge, attitudes towards, and beliefs about contraception (n = 11). When making contraceptive decisions, women with higher BMIs may consider ease of use [ 54 ] and side effect profile [ 46 , 57 , 64 ]. For instance, a study by Chuang et al [ 64 ] revealed that women with higher BMIs expressed concerns about potential weight gain associated with hormonal methods of contraception.…”
Section: Resultsmentioning
confidence: 99%
“…All of the above complications and especially hypertension are more common in obese teens. Concerning the use of contraception in obese patients, it should be mentioned that there is contraceptive protection regardless of the BMI size (lower rates of undesirable pregnancies) [ 27 , 28 ].There is limited and unclear information concerning the use of oral contraceptives in obese patients. The risk of deep vein thrombosis in obese patients is doubled.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of deep vein thrombosis in obese patients is doubled. However, the additional absolute risk of venous thrombosis following the use of combined low-dose contraceptives is rather limited and certainly less than the corresponding risk due to pregnancy and periodontal disease [ 27 , 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%